2022
DOI: 10.1021/jacs.2c09487
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Metal–Organic Framework (MOF) Topology by Regulating Ligand and Secondary Building Unit (SBU) Geometry: Structures Built on 8-Connected M6 (M = Zr, Y) Clusters and a Flexible Tetracarboxylate for Propane-Selective Propane/Propylene Separation

Abstract: Topology evolution originating from variations of linker and SBU (Secondary Building Unit) geometries could largely enrich the chemistry of metal−organic frameworks (MOFs). Here we report the synthesis and characterization of three MOF structures built on the same organic linker, N,N,N′,N′-Tetrakis(4-carboxyphenyl)-1,4-phenylenediamine (tcppda) and similar 8-connected M 6 (M = Zr or Y) clusters. The three compounds, HIAM-402, HIAM-403, and HIAM-311, feature 4,8-connected sqc, scu, and flu topology, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 38 publications
2
29
0
Order By: Relevance
“…In general, the 1,4-bis­(diphenylamino)­benzene (DAB) unit can adopt two configurations: one is square with C 2 h symmetry, and the other is tetrahedral with D 2 d symmetry (Figure S1). Both configurations of DAB have been seen in single-crystal X-ray structures of metal–organic frameworks assembled from the tetracarboxylate linkers containing the DAB unit. , The structure of TPDT-COF was modeled as a sevenfold diamond ( dia ) topology based on the geometrical connectivity of the two individual units. The experimental PXRD pattern showed good agreement with the calculated one based on the structural model (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…In general, the 1,4-bis­(diphenylamino)­benzene (DAB) unit can adopt two configurations: one is square with C 2 h symmetry, and the other is tetrahedral with D 2 d symmetry (Figure S1). Both configurations of DAB have been seen in single-crystal X-ray structures of metal–organic frameworks assembled from the tetracarboxylate linkers containing the DAB unit. , The structure of TPDT-COF was modeled as a sevenfold diamond ( dia ) topology based on the geometrical connectivity of the two individual units. The experimental PXRD pattern showed good agreement with the calculated one based on the structural model (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…7a), which is built on an 8-connected hexanuclear Zr 6 cluster and tetrakis(4-carboxyphenyl)-1,4-phenylenediamine and features an sqc topology. 34 HIAM-402 possesses a highly robust framework as well as high porosity and exhibits selective adsorption of propane over propylene. Single-component adsorption isotherms revealed that propane is notably favored at low pressure compared to propylene although the saturation uptakes at 1 bar are similar for the two gases (Fig.…”
Section: Propane-selective Separation For Propylene Purificationmentioning
confidence: 99%
“…(b) Single-component adsorption-desorption isotherms of propane/propylene adsorption isotherms at 298 K. (c) Dynamic breakthrough curves of HIAM-402 for propane/propylene at 298 K and 1 bar. Optimized configuration of adsorbed propylene (d) and propane (e) in the channel of HIAM-402 by ab initio calculations.Reproduced with permission 34. Copyright 2022, American Chemical Society.…”
mentioning
confidence: 99%
“…[13,14] Metal-organic frameworks (MOFs) as a newer family of porous adsorbents are particularly desirable in addressing industrially challenging separations of hydrocarbons because of their diverse structural modularity, exceptional porosity, highly tunable pore size, pore shape, and surface functionality. [15][16][17][18] These unique features of MOFs have led to their excellent performance for the separation of physically and chemically similar mixtures including olefin/ paraffin, [19][20][21][22][23] alkyne/olefin, [24,25] carbon dioxide/ acetylene, [26][27][28] and alkane isomers. [29,30] In particular, the successful practice of reticular chemistry has enabled the precise control of pore structures of MOFs, affording adsorbents with desired discrimination capability toward C6 alkane isomers with different degrees of branching (Table 1).…”
Section: Introductionmentioning
confidence: 99%